Bacteriological Quality of Groundwater in Imiringi Town, Bayelsa State, Nigeria - Idah Seiyaboh, Enetimi; Okponanabofa Youkparigha, Felix; Chibueze Izah, Sylvester; Deborah Daniels, Ikpilavi (Journal of Biotechnology and Biomedical Science, 2020)
This study evaluated the bacteriological quality of groundwater from Imiringi in Ogbia Local government area of Bayelsa State, Nigeria. Groundwater samples were obtained in triplicates from four locations in the study area and analyzed for the bacteria quality using standard protocols. Results showed that the microbial density ranged from 2.97 – 6.03 x 104 cfu/ml (for total heterotrophic bacteria counts), 4.17 – 5.43 x 102 cfu/ml (for Enterobacteriaceae bacteria counts) and 0.00 – 1.48 x 102 cfu/ml (for Salmonella-Shigella counts). Statistically, there was no significant difference (p>0.05) across the various locations for each of the parameters. The density observed were higher than the allowable limit of 1.0 x 102 cfu/ml for drinking water as recommended by World Health Organization/Food and Agricultural Organization, and maximum permissible level of 10cfu/ml for total coliform as specified by Standard Organization of Nigeria. The prevalence of bacteria isolated in the water samples were Aeromonas species (8.00%), Citrobacter species (7.50%), Escherichiacoli (20.75%), Klebsiella species (5.50%), Pseudomonas species (12.00%), Salmonella species (2.25%), Shigella species (3.25%) and Staphylococcus species (40.75%). From the bacteria density and diversity, the water is not potable. Some of the bacterial found are of public health importance. Hence, there is a need to adequately treat the water using chlorination and boiling techniques before drinking.
Keywords: Bayelsa state; Environmental contaminants; Microorganisms; Public health; Water quality